A Literature Review: Acute Tonsillitis - Azzahra, Anis Aura; Khotimah, Andi Husnul; Sugiono, Muhammad Rafly Adrian; Zulkifli, Yasmin Sabrina (Jurnal Biologi Tropis, 2025)
Acute tonsillitis is a bacterial infection characterized by painful swallowing, swelling, and redness of the tonsils. The purpose of this literature review is to improve understanding of acute tonsillitis, which is essential for patient care and a favorable prognosis. The method used is a systematic literature review. The results of this literature review indicate that tonsillitis is a common inflammatory condition affecting the palatine tonsils, accounting for approximately 1.3% of outpatient visits. The condition is typically caused by viral or bacterial infections and manifests with symptoms such as sore throat, fever, odynophagia, and tonsillar erythema or exudate. Viral tonsillitis is often self-limiting; however, bacterial causes most notably Streptococcus group A can lead to significant complications, including peritonsillar abscess, acute rheumatic fever, and poststreptococcal glomerulonephritis. Prompt and accurate diagnosis is essential to distinguish viral from bacterial etiologies. Clinical scoring systems, such as the Centor or McIsaac criteria, and microbiological testing, help guide appropriate management and reduce unnecessary antibiotic use. Early identification and intervention are critical to preventing complications and promoting effective recovery. In conclusion, the prognosis for acute tonsillitis is generally good, with most cases healing on their own without complications.